2018
DOI: 10.1253/circj.cj-17-0712
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Platelet Count and Postoperative Blood Loss in Patients Undergoing Cardiac Surgery With Cardiopulmonary Bypass and Fresh Frozen Plasma Administration Guided by Thromboelastometry

Abstract: Background: Coagulopathy after cardiopulmonary bypass (CPB) is caused by multiple factors, including reduced coagulation factors and a low platelet count. Methods and Results:In this study, we undertook a post hoc analysis to identify factors associated with increased postoperative blood loss in 97 patients undergoing cardiac surgery with CPB, with fresh frozen plasma administered according to a ROTEM-guided algorithm. We identified 24 patients for the top quartile of postoperative blood loss, >528 mL and defi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 35 publications
(13 reference statements)
0
17
0
Order By: Relevance
“…In a previous observational study of children undergoing cardiac surgery, lower platelet count during cardiopulmonary bypass was the variable most significantly associated with intraoperative and 12-hour blood loss in linear regression analysis (cutoff value was platelet count of 108 x 10 9 /L) [11]. Other observational studies showed that lower post-bypass platelet count independently predicted early postoperative blood loss [12][13][14].…”
Section: Investigation Of Factors Associated With Bleeding After Cabgmentioning
confidence: 91%
“…In a previous observational study of children undergoing cardiac surgery, lower platelet count during cardiopulmonary bypass was the variable most significantly associated with intraoperative and 12-hour blood loss in linear regression analysis (cutoff value was platelet count of 108 x 10 9 /L) [11]. Other observational studies showed that lower post-bypass platelet count independently predicted early postoperative blood loss [12][13][14].…”
Section: Investigation Of Factors Associated With Bleeding After Cabgmentioning
confidence: 91%
“…Cardiopulmonary bypass (CPB) has always been considered as the primary cause of perioperative thrombocytopenia (TCP) after cardiac surgery [1,2]. Recently, TCP has been specifically reported after biological aortic valve replacement (AVR) [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Correlations between bleeding and platelet counts and aggregations are well-known [19]. In our study, we calculated and analyzed MCE platelet component in ROTEM, which reflects actual clot strength contributed by platelets.…”
Section: Discussionmentioning
confidence: 98%